Low Homeownership in Germany - A Quantitative Exploration - Leo Kaas; Georgi Kocharkov; Edgar Preugschat; Nawid Siassi (Center for Economic Studies and ifo Institute (CESifo), 2017)
The homeownership rate in Germany is one of the lowest among advanced economies. To better understand this fact, we analyze the role of three specific policies which discourage homeownership in Germany: an extensive social housing sector with broad eligibility criteria, high transfer taxes when buying real estate, and no tax deductions for mortgage interest payments by owner-occupiers. We build a lifecycle model with uninsurable income risk and endogenous homeownership in order to quantify the policy effects on homeownership and welfare. We find that all three policies have sizable effects on the homeownership rate. At the same time, household welfare would be reduced by moving to a policy regime with low transfer taxes and mortgage interest tax deductions, but it would improve in the absence of social housing, in particular when coupled with housing subsidies for low-income households.
Keywords: D15; E21; R21; R38; 330; homeownership; housing markets